NEWS BRIEFS. (America Magazine: The Jesuit Review of Faith & Culture, 2012)
The article offers news briefs related to Christianity, that include the postponement of a papal delegation that was scheduled to visit Damascus, Syria, Flooding at the Shrine of Our Lady of Lourdes, and the expulsion of Bishop Richard Williamson of Great Britain from the Society of St. Pius X.